Curcumin-loaded composite aerogel as well as preparation method and application thereof

The loaded curcumin aerogel prepared by combining pineapple leaf cellulose and chitosan solves the problems of curcumin stability and shelf life of aquatic products, realizes the sustained release of curcumin antioxidant and water absorption and oil absorption effects of curcumin, and extends water The shelf life of the product and improves the freshness of the food.

CN119302350APending Publication Date: 2025-01-14GUANGDONG OCEAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411722177.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The application of curcumin in the food field is limited by its poor photosensitive and stability, and existing preservation methods cannot effectively extend the shelf life of aquatic products, especially the problem of spoilage caused by blood water accumulation and lipid oxidation is difficult to solve.

Method used

The composite aerogel loaded with curcumin was prepared by combining pineapple leaf cellulose and chitosan. The sol-gel method combined with freeze-drying technology is used to form an aerogel with antibacterial, water-absorbing and oil-absorbing effects, which is used to extend meat products. Shelf life.

Benefits of technology

Effectively release curcumin, prolong the shelf life of aquatic products, significantly slow down lipid oxidation and blood water accumulation, improve the freshness and nutritional value of food, and provide environmentally friendly freshness solutions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005158319670000071
    Figure BDA0005158319670000071
  • Figure BDA0005158319670000072
    Figure BDA0005158319670000072
  • Figure HDA0005158319680000011
    Figure HDA0005158319680000011
Patent Text Reader

Abstract

The invention discloses curcumin-loaded composite aerogel as well as a preparation method and application thereof, and relates to the technical field of composite aerogel preparation, pineapple leaf cellulose is obtained from pineapple leaves, then the pineapple leaf cellulose and chitosan are compounded to obtain a hydrogel solution, a curcumin solution is added into the hydrogel solution, uniform mixing and freeze drying are performed, and the curcumin-loaded composite aerogel is prepared. The chitosan / pineapple leaf cellulose antibacterial aerogel is prepared by combining a sol-gel method with freeze drying, and curcumin can be effectively released to slow down the putrefaction degree of meat products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite aerogel preparation, and in particular to a composite aerogel loaded with curcumin, and a preparation method and application thereof. Background Art

[0002] Curcumin (Cur) is a hydrophobic polyphenolic compound with a wide range of sources and has anti-inflammatory, anticancer, antibacterial and antioxidant activities. [1] However, the high photosensitivity, poor water solubility and stability of curcumin greatly limit its application in the food field. Therefore, it is necessary to develop a loading mechanism to improve this, in which a curcumin-loaded composite aerogel can be designed to protect curcumin from external deterioration factors.

[0003] At present, it is still a difficult task to extend the shelf life of aquatic products. Generally, golden pomfret shows obvious spoilage after 9 days of refrigeration at 4°C. The reason for this phenomenon is the accumulation of blood and water in fresh meat, oxidation of protein and lipids, the influence of endogenous enzymes and microorganisms, and finally the sensory value and nutritional safety of aquatic products are seriously reduced. Therefore, it is necessary to explore an effective method to solve the above problems in the preservation process of fish and shrimp. The research on composite functional materials combining food packaging materials and antimicrobial active substances is getting more and more popular. After adding antimicrobial agents to whey protein isolate / chitosan aerogel, the shelf life of chicken stored at 7°C can be extended to 4 days; corn straw cellulose nanocrystals / acetylated starch-based aerogels prepared by Wang, Nan et al. as a fresh-keeping pad for meat can significantly extend the shelf life of chilled beef; the use of agricultural waste to develop food packaging materials can absorb excess water to a certain extent, and the release of biological activity slows down lipid oxidation and improves the nutritional value of minced beef. The reasons that affect the freshness of refrigerated meat products in the above-mentioned practical applications include lipid oxidation and excessive accumulation of blood and water. The meat trays in most retail stores are ordinary oil-proof plastic mats with poor blood and water absorption performance. Excess blood and water become an environment for the growth and reproduction of microorganisms in the tray-packaged meat products, which is an important factor that shortens the storage period of meat products.

[0004] In response to these problems, it is urgent to develop a new food-grade pad for meat that can better absorb blood and water. Aerogel is well-known for its low density, high surface area and large porosity. It has a loose three-dimensional mesh porous structure inside, which can absorb and retain water. It is also an excellent carrier for antibacterial agents. Multifunctional aerogel based on natural ingredients has excellent absorption performance, sustained release of antibacterial agents, antioxidant effect and environmental friendliness as a fresh meat pad. Therefore, the use of aerogel as an absorbent pad for fresh meat preservation has brought new opportunities for meat preservation. To ensure the safety of aerogel in meat product preservation, it is very important to choose harmless and non-toxic raw materials for construction. Chitosan (CS) is a natural alkaline polysaccharide with amino and hydroxyl functional groups. It is a natural material for constructing a network pore structure. Since the mechanical properties of aerogels prepared from a single biopolymer are poor, two or more substrates are used to prepare aerogels in many current studies. Cellulose is one of the most common polysaccharides in nature. It contains abundant hydroxyl groups, which have good affinity and active sites for inorganic nanoparticles. It is a natural material that can improve the structural stability of pure chitosan aerogel. Among agricultural wastes, pineapple leaves contain a large amount of cellulose. The carboxyl functional groups introduced by 2,2,6,6-tetramethylpiperidinyloxy (TEMPO) oxidation are conducive to enhancing the binding ability between cellulose and chitosan groups. The formation of polymers can greatly improve the mechanical properties of aerogels and show good pressure resistance. Therefore, how to prepare a composite aerogel loaded with curcumin suitable for food preservation is worth studying. Summary of the invention

[0005] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide a composite aerogel loaded with curcumin and a preparation method and application thereof.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing a composite aerogel loaded with curcumin comprises the following steps: obtaining pineapple leaf cellulose from pineapple leaves, then compounding the pineapple leaf cellulose with chitosan to obtain a composite aerogel, adding a curcumin solution into the composite aerogel, mixing, and freeze-drying to obtain the composite aerogel.

[0008] As a preferred embodiment of the present invention, a specific method for obtaining pineapple leaf cellulose from pineapple leaves comprises the following steps:

[0009] S1: crushing pineapple leaves to obtain pineapple leaf powder, then mixing the pineapple leaf powder and alkali solution for digestion, filtering and washing with distilled water to obtain slurry;

[0010] S2: bleaching the pulp with a mixed solution of H2O2 and NaOH at 70-90°C for 0.5-1.5h, filtering, washing with distilled water, and drying to obtain pineapple leaf cellulose;

[0011] S3: Dissolve TEMPO and NaBr in distilled water, add pineapple leaf cellulose and NaClO solution successively, adjust the pH to 9-11 with sodium hydroxide solution, filter and wash the solution solid with distilled water until neutral to obtain the product; disperse the product in water to prepare a suspension, obtain nanofiber suspension by ultrasound, and obtain pineapple nanocellulose after freeze-drying.

[0012] As a preferred embodiment of the present invention, in step S1, the alkali solution is a sodium hydroxide solution with a concentration of 2-4 wt%, and / or washing is performed 2-4 times.

[0013] As a preferred embodiment of the present invention, in step S2, the mass ratio of H2O2 to NaOH is 9-11:1, and the drying temperature is 70-90°C.

[0014] As a preferred embodiment of the present invention, in step S3, the pH value of the NaClO solution is 9-11, and the concentration is 4-6wt%;

[0015] The molar ratio of TEMPO and NaBr is 1:1-3;

[0016] The mass volume ratio of pineapple leaf cellulose and NaClO solution is 1 mg:4-6 mL.

[0017] As a preferred embodiment of the present invention, the concentration of the curcumin solution is 10-50 mg / mL, specifically, curcumin is dissolved in anhydrous methanol, Tween 80 and water.

[0018] As a preferred embodiment of the present invention, the mass ratio of the pineapple leaf cellulose to chitosan is 1-4:6:9.

[0019] As a preferred embodiment of the present invention, freeze drying is specifically pre-freezing at -20°C for 10-14 hours, freezing again at -80°C for 3-5 hours, and vacuum freeze drying for more than 36 hours.

[0020] The invention also discloses a curcumin composite aerogel, which is prepared by any of the above preparation methods.

[0021] The invention also discloses an application of the curcumin composite aerogel in preparing a food preservative.

[0022] The beneficial effects of the present invention are: the chitosan / pineapple leaf cellulose antibacterial aerogel is prepared by combining the sol-gel method with freeze-drying, and curcumin can be effectively released to achieve the effect of prolonging the freshness of meat products; in addition, the aerogel prepared by the present invention also has the effects of antibacterial and water and oil absorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Figure 2. Preparation of food preservation meat pads using aerogels with different chitosan contents;

[0024] Figure 2 The DPPH scavenging activity test results at different oxidation times;

[0025] Figure 3 The results of curcumin release and cumulative release at different times;

[0026] Figure 4 The water and oil absorption results of different samples;

[0027] Figure 5 Infrared characterization structure of different samples;

[0028] Figure 6 The antibacterial results of different samples are shown in Figure 2.

[0029] Figure 7 The appearance effects of different sample treatments on prawns and golden pomfret;

[0030] Figure 8 The test results of weight loss ratio, color difference, pH value and volatile basic nitrogen of shrimp and golden pomfret treated with different samples;

[0031] Fig. 9 Analysis of flavor components after shrimp treatment for different samples;

[0032] Fig.10 Analysis of flavor components of golden pomfret after different sample processing. DETAILED DESCRIPTION

[0033] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0034] The materials used in the following examples are as follows:

[0035] Pineapple leaves were collected from Xuwen, Zhanjiang, Guangdong; chitosan; curcumin; sodium hydroxide; hydrogen peroxide; TEMPO; anhydrous methanol; Tween 80; glacial acetic acid; LB broth medium; agar.

[0036] TEMPO: 2,2,6,6-tetramethylpiperidinyl-N-oxide.

[0037] Example 1

[0038] (1) Preparation of CS / CNF composite aerogels

[0039] The pineapple leaf cellulose was prepared by alkaline digestion-hydrogen peroxide bleaching-TEMPO oxidation of pineapple leaves and stored in a desiccator.

[0040] The specific steps are as follows: the pineapple leaves are processed into powder using an ultrafine grinder in advance, and then mixed with a 3wt% NaOH solution for digestion, digestion, filtration, and distilled water washing, and this process is repeated twice. Bleaching: The mixed solution of H2O2:NaOH (weight ratio is 10:1) is bleached at 80°C for 1h, then filtered and washed with distilled water, and dried in an oven at 80°C to obtain pineapple leaf cellulose. Reducing agent: 1mmol TEMPO and 1mmol NaBr are dissolved in distilled water, 1g pineapple cellulose and 5mL 5wt% NaClO solution with a pH of 10 are added successively, the pH is adjusted to 10 with a sodium hydroxide solution, and then the solution solid is washed with distilled water until it is neutral to obtain the product. The product is dispersed in water and prepared into a 0.1wt% suspension, and a transparent nanofiber suspension is obtained by ultrasonication with a cell disruptor, and pineapple nanocellulose is obtained after freeze-drying.

[0041] A certain amount of pineapple leaf cellulose was weighed and treated with a cell ultrasonic crusher (power 20%, 5min) until the cellulose was evenly dispersed in the acetic acid solution, chitosan was added and stirred with a magnetic stirrer for 40min, and then poured into a mold for pre-freezing and freeze drying for more than 36h to obtain CS / CNF composite aerogel. Composite aerogel according to the CS / CNF ratio (CS: CNF = 80:20).

[0042] (2) Preparation of CS / CNF-Cur aerogel

[0043] The specific operation is as follows: 100 mg of curcumin (Cur) is shaken to dissolve it in 300 μL of anhydrous methanol, 200 μL of Tween 80 and a small amount of water to form a curcumin solution. The above-prepared curcumin solution is diluted to concentrations of 10, 30, and 50 mg / mL and added to the CS / CNF composite aerogel prepared in (1), and stirred on a magnetic stirrer for 10 minutes until the components in the solution are evenly mixed to obtain a mixed hydrogel. The mixed hydrogel is then poured into a film mold, pre-frozen at -20°C for 12 hours, frozen again at -80°C for 4 hours, and freeze-dried for more than 36 hours. The curcumin composite aerogels of different concentrations (10, 30, 50 mg / mL) prepared in the example are named CS / CNF-Cur1, CS / CNF-Cur2, and CS / CNF-Cur3, respectively.

[0044] Food preservation meat pads were prepared using aerogels with different chitosan contents (0%, 20%, 40%, 60%, 80%, 100%). The results are shown in Figure 1As can be seen from the figure, the mechanical properties of pure chitosan and pure cellulose aerogels are poor, and they show phenomena such as collapse, deformation, and material detachment. The composite aerogel with a CS / CNF ratio (chitosan ratio is 80%) is more stable than the composite aerogels with other ratios as confirmed by thermogravimetric analysis. The CS / CNF composite aerogel with this ratio is used to prepare the CS / CNF-Cur composite aerogel type fresh-keeping pad for subsequent fresh-keeping tests.

[0045] (3) Antioxidant test and sustained release experiment

[0046] DPPH free radical scavenging experiment: Weigh 5 mg of curcumin aerogel samples CS / CNF-Cur1, CS / CNF-Cur2, and CS / CNF-Cur3, mix with 5 mL of freshly prepared 0.1 mM DPPH / ethanol solution (0.00394 g / 100 mL), shake for 15 seconds, and place in the dark for 10, 20, 40, 60, 120, 720, 1 440, and 2880 minutes. When the reaction is completed, remove the supernatant in time, measure its absorbance at 515 nm using an ELISA reader, and replace the test sample with an equal amount of ethanol as a blank control. The DPPH free radical scavenging rate is calculated according to the formula:

[0047]

[0048] Wherein: A0 is the absorbance of the blank solution; A1 is the absorbance of the DPPH radical solution after adding aerogel.

[0049] pH 7.4 PBS buffer (0.27 g sodium dihydrogen phosphate; 1.42 g sodium hydrogen phosphate; 8 g sodium chloride; 0.2 g potassium chloride / 1L deionized water): ethanol (7:3) was used as the release medium to simulate the in vitro release of curcumin composite aerogels. At room temperature, an equal amount of curcumin composite aerogels was added to 20 mL of the release external solution and stirred. After that, 200 uL of the dialysate was taken at 1 h, 2 h, 3 h, 6 h, and 8 h to determine the Cur content. The volume of the solution must remain unchanged. The cumulative release rate (Q) formula is as follows:

[0050] Zero-level model: C = K o t;

[0051] Q n =C n *V0+(C1+C2+...C n -1)*V;

[0052]

[0053] Where C is the cumulative release amount of curcumin at release time t, K ois the release constant for constructing the model; Vo is the total volume of the dialysis medium (L), Cn is the curcumin concentration measured at sampling point n (mg / L), Ci is the concentration measured at sampling point i (mg / L), and V is the sampling volume (L)

[0054] The antioxidant test results of curcumin composite aerogel are shown in Figure 2 The composite aerogels encapsulating curcumin have high antioxidant capacity, and the PDDH free radical scavenging rate can reach more than 85%. The oxidation effect of the three composite aerogels is related to the oxidation time, and has a low dependence on the curcumin concentration content of the sample. Even at low concentrations, it still has antioxidant potential after 180 minutes. Within 20 minutes, the composite aerogels with 50 mg / mL curcumin can be quickly released into the solution, and the clearance rate rises rapidly. After reaching the highest clearance rate, it tends to dynamic equilibrium, which is positively correlated with the release amount of curcumin in the composite aerogels.

[0055] The test results of curcumin sustained release into PBS / ethanol solution are shown in Figure 3 It can be seen that the model determination coefficient (R 2 ) is higher (R 2 =0.83554), indicating that the release model is suitable for the sustained release of curcumin in composite aerogels at low concentrations. A burst release phenomenon occurred in the 50 mg / mL composite aerogel within 30 min. This is because the curcumin content on the surface of the aerogel is high, the release amount is high at the beginning, and then tends to be stable. When released to 5-7 h, the volume expansion of the aerogel hinders the diffusion of curcumin due to its certain water absorption performance, thereby reducing the cumulative release of curcumin in the solution.

[0056] (4) Characterization of composite aerogels

[0057] The water and oil absorption properties of different composite aerogels are shown in Figure 4 It can be seen that the aerogel has excellent water and oil absorption capabilities, with the highest absorption rate reaching 3006.67% and 2080.00%. Compared with CS / CNF aerogel, the addition of curcumin affects the absorption performance to a certain extent, which is related to the water solubility of curcumin. The more curcumin content, the greater the load on the aerogel surface and internal pores, and the lack of channels and hydrophilic surfaces that can absorb water and oil. This phenomenon mainly occurs because curcumin covers the absorption functional groups of the aerogel. As the concentration of curcumin increases, the water and oil absorption performance of the composite aerogel will decrease.

[0058] Infrared spectrum of curcumin composite aerogel Figure 5 , 3426, 2904, 1604 and 1095cm -1The characteristic peaks at the 100 nm and 100 nm are caused by -OH stretching vibration, -CH bond stretching, CN bond bending vibration and -CO stretching vibration. Compared with CS / CNF, the peaks of this group in the curcumin composite aerogel have changed significantly. This is because curcumin will change the chemical bonds with O, N and other groups in the material. With the increase of curcumin, the benzene ring double bond (1504cm -1 ) and aromatic single bond CO (1274cm -1 )The more obvious the functional group absorption peak is, the more curcumin is loaded on the composite aerogel, and these active groups can be better retained.

[0059] (5) Antibacterial properties of curcumin composite aerogel

[0060] Escherichia coli and Staphylococcus aureus frozen at -80°C were inoculated into 30mL LB broth medium and cultured at 30°C for 24h for activation. After the cultured bacterial suspension was diluted with saline, the CS / CNF-Cur composite aerogel was added to the bacterial suspension and cultured in a shaker at 30°C for 10h. The sample was then diluted with saline to form bacterial suspensions of different concentrations, and 100μL of the bacterial suspension was evenly spread on the LB agar medium and inverted and incubated at 30°C for 24h.

[0061] Curcumin was used as an antibacterial substance to prepare antibacterial aerogel pads with excellent adsorption and mechanical properties. The antibacterial effects of antibacterial aerogels with different curcumin concentrations on Staphylococcus aureus and Escherichia coli were shown in Figure 2. Figure 6 As shown. The results showed that the prepared aerogel showed antibacterial activity against both bacteria. The curcumin inside can be slowly released into the environment, inhibiting the cell's efflux pumps, causing toxic substances in the bacteria to accumulate inside the cells, thereby damaging the integrity of the cells and causing cell osmotic imbalance.

[0062] (6) Preservation effect of fresh fish and shrimp

[0063] The golden pomfret and shrimp samples were placed in a 4°C refrigerator with a CS / CNF-Cur aerogel fresh-keeping pad. The physical and chemical indicators of the fish and shrimp meat samples were measured at 7 days, including the color, pH value, mass loss, flavor component changes and total volatile salt nitrogen (TVB-N) of the fish meat.

[0064] The results of the quality changes of shrimp and golden pomfret preserved by curcumin composite aerogel are shown in Figure 8(A) It is obvious that the weight loss ratio of each group of shrimp has decreased and the difference between groups is small. This is because the shrimp shell has a certain effect of isolating the external environment. Fresh shrimp meat will reduce the water holding capacity of the muscle under the action of endogenous enzymes. At this time, the composite aerogel can only absorb the liquid on the surface of the shrimp body and in the tray. After 7 days of storage, the weight of the fish samples in the treatment group has been lost. This is due to the composite aerogel absorbing the water, fat and other substances lost by the fish meat, resulting in a reduction in weight. The weight loss ratio of the control group is 104.86±6.02. The reason for this phenomenon may be the accumulation of gravy, and the water vapor in the refrigerator adheres to the meat, causing its weight to increase.

[0065] The color difference between shrimp and fish is shown by ΔE (color difference value). Figure 8 As shown in (B), during the storage of shrimp, obvious black blocks can be seen in the shrimp heads of the untreated group. This is because under the catalysis of polyphenol oxidase, the monophenol in the shrimp body will oxidize to form colorless diphenols. The quinones formed by continued oxidation are easy to combine with proteins or amino acids to form brown complexes, which will cause the shrimp body to lose its luster and gradually turn black. The main reason for the obvious lighter color of CS / CNF-Cur3 shrimp is the aging of the meat. In general, the color difference of the treated groups is smaller than that of the control group, indicating that the aerogel meat pad can play a certain antioxidant role, and the most significant effect is the shrimp treated with CS / CNF-Cur2. Figure 7 This is the appearance picture of golden pomfret after storage for 7 days. During the refrigeration process, the ferrous ions in the myoglobin hemoglobin of the fish meat were oxidized into ferric ions. The oxidized metmyoglobin in the fish meat of the untreated group made the fish meat appear obviously black. This time it was the fish meat treated with CS / CNF. The color of the fish meat treated with curcumin aerogel was better retained.

[0066] The initial pH values ​​of shrimp and golden pomfret before treatment were between 7.07-7.22 and 6.89-7.02, respectively. The pH of fresh shrimp tissue was about 7.2, and the pH of fresh fish was 6.5-6.8. Figure 8As shown in (C), during the storage process, the pH values ​​of the aerogel shrimp treatment group and the blank group increased, which was related to the degree of shrimp corruption and the increase in the total content of putrescine, cadaverine and biogenic amines in the shrimp. After 7 days of cold storage, the pH value of the shrimp in the CS / CNF-Cur2 group was lower than that of the others. Since shrimps belong to crustacean arthropods, the aerogel pad treatment can absorb the surface liquid, which is still challenging to reduce the corruption of the internal meat and can slow down the corruption of shrimps to a certain extent. The fish meat directly contacts the composite aerogel pad, and the pH value of the treatment group is lower than that of the blank group. The surface aerogel pad can release curcumin while absorbing the meat juice, thereby reducing the degree of meat corruption. It is worth noting that the pH of fish meat will first decrease and then increase. This is because glycogenolysis, fat oxidation and ATP degradation will occur in the early stage of cold storage, and the acidic substances produced will affect the pH value of fish meat together with amino acids, ammonia and amines. At this time, the pH values ​​of the aerogel-treated samples were all lower than 6.79, indicating that the samples were still in a sub-fresh state. This was attributed to the excellent water and oil absorption properties of aerogel, which reduced the moisture required for the growth of spoilage microorganisms, and the release of antioxidants, which was beneficial to the preservation of fish.

[0067] TVB-N value is an important indicator for judging the freshness of aquatic products during storage. When the TVB-N level exceeds 25 mg / 100 g, the aquatic product has deteriorated. Figure 8 As shown in (D), the shrimp was completely corrupted at 7 days, followed by the CS / CNF-Cur3 treatment group (34.16 mg / 100 g), and the TVB-N values ​​of the other treatment groups were all below 25 mg / 100 g. Compared with shrimp, fish is less likely to be corrupted, which is mainly related to the fact that shrimp contains more free amino acids and water. After 7 days of storage, the TVB-N value of the golden pomfret in the control group was 13.72 mg / 100 g, and the TVB-N value of the treatment group was effectively suppressed. At this time, the samples were all in a fresh state. The results show that the curcumin composite aerogel can effectively inhibit the formation of basic nitrogen by absorbing excess water, slowly releasing curcumin, and adjusting the storage environment, thereby extending the shelf life of aquatic products.

[0068] The changes of flavor components of golden pomfret and shrimp preserved by composite aerogel Fig. 9 and Fig.10 , trimethylamine oxide (to maintain the osmotic pressure balance with seawater, stabilize the body's protein against the hydrostatic pressure of the deep sea, and has a umami taste) will be reduced to trimethylamine and dimethylamine under the action of microorganisms after the death of aquatic products. These two have a strong fishy smell. At the same time, unsaturated fatty acids in aquatic products can also be decomposed into aldehydes, alcohols, ketones and other volatile substances with fishy smell. PCA analysis of electronic nose data of shrimp and fish after 7 days of preservation Fig. 9 and Fig.10As shown in the figure, the contribution rates of PC1 were 61.0% and 74.9%, the contribution rates of PC2 were 27.5% and 11.5%, and the cumulative contribution rates were 88.5% and 86.4%, covering most of the information of shrimp and fish samples. The results can accurately reflect the flavor characteristics of shrimp and golden pomfret. The shrimp samples after 7 days were closer to the CS / CNF-1 group, while the other treatment groups were far away from the CK group, indicating that the flavor components of other treatment groups were quite different. Similarly, the untreated golden pomfret group was closest to CS / CNF, indicating that the volatile components of the two samples were similar. The distances from the treatment groups to CK from near to far were CS / CNF-Cur1, CS / CNF-Cur3, and CS / CNF-Cur2.

[0069] In order to further analyze the differences in volatile flavor components of shrimp and fish prepared with different fresh-keeping composite aerogels, radar charts were drawn for comparison. Fig. 9 It can be seen that the response values ​​of shrimp in W1W, W2S and W5S sensors are more obvious, followed by W1C and W1S. These volatile substances are the main components of fishy and corrupted smells in aquatic products, including sulfides, terpenes and nitrogen oxides. Among them, sulfide indicated by W1W is the main fishy smell component. It is obvious that the fishy smell formation of shrimp treated with CS / CNF and CS / CNF-Cur1 is inhibited to a certain extent. Fig.10 It is obvious from the radar chart that the fish meat in the CK and CS / CNF groups is more seriously spoiled, with the highest perceived values ​​at W2S and W5S, which are mainly alcohols, alkanes and some aromatic compounds produced by the oxidation of unsaturated fats. The various components of fish meat in the curcumin composite aerogel pad are lower than those in CK, indicating that this preservation method can inhibit the oxidation and decomposition rate of umami substances in fish meat to a certain extent, and reduce the degree of fish meat spoilage. In summary, the composite aerogel is not as good as cut meat products in preserving crustacean aquatic products. The shrimp shell not only isolates the contact with the outside air, but also blocks the aerogel absorption and release of antioxidant substances.

[0070] Therefore, the present invention pre-extracts pineapple leaf cellulose and TEMPO-oxidizes it, and then uses freeze-drying to prepare an antibacterial composite aerogel with excellent absorption performance, which slowly releases curcumin to achieve antibacterial effect. Golden pomfret and prawns were preserved at 4°C. After 7 days, compared with the untreated group, the curcumin composite aerogel absorption pad can effectively absorb excess moisture from fish and shrimp, slowing down the degree of corruption of aquatic products. This method provides an effective solution for preserving fresh aquatic products.

[0071] The above-mentioned embodiments only express the preferred implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all these changes and deformations should fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a composite aerogel loaded with curcumin, characterized in that: Pineapple leaf cellulose is obtained from pineapple leaves, and then the pineapple leaf cellulose is compounded with chitosan to obtain a composite aerogel, and a curcumin solution is added to the composite aerogel, mixed, and freeze-dried to obtain the composite aerogel.

2. The method for preparing a composite aerogel loaded with curcumin according to claim 1, characterized in that: The specific method for obtaining pineapple leaf cellulose from pineapple leaves comprises the following steps: S1: crushing pineapple leaves to obtain pineapple leaf powder, then mixing the pineapple leaf powder and alkali solution for digestion, filtering and washing with distilled water to obtain slurry; S2: bleaching the pulp with a mixed solution of H2O2 and NaOH at 70-90°C for 0.5-1.5h, filtering, washing with distilled water, and drying to obtain pineapple leaf cellulose; S3: Dissolve TEMPO and NaBr in distilled water, add pineapple leaf cellulose and NaClO solution successively, adjust the pH to 9-11 with sodium hydroxide solution, filter and wash the solution solid with distilled water until neutral to obtain the product; disperse the product in water to prepare a suspension, obtain nanofiber suspension by ultrasound, and obtain pineapple nanocellulose after freeze-drying.

3. The method for preparing a composite aerogel loaded with curcumin according to claim 2, characterized in that: In step S1, the alkali solution is a sodium hydroxide solution with a concentration of 2-4 wt%, and / or washing is performed 2-4 times.

4. The method for preparing a composite aerogel loaded with curcumin according to claim 2, characterized in that: In step S2, the mass ratio of H2O2 to NaOH is 9-11:1, and the drying temperature is 70-90°C.

5. The method for preparing a composite aerogel loaded with curcumin according to claim 2, characterized in that: In step S3, the pH value of the NaClO solution is 9-11, and the concentration is 4-6wt%; The molar ratio of TEMPO and NaBr is 1:1-3; The mass volume ratio of pineapple leaf cellulose and NaClO solution is 1 mg:4-6 mL.

6. The method for preparing a composite aerogel loaded with curcumin according to claim 1, characterized in that: The concentration of the curcumin solution is 10-50 mg / mL, specifically, curcumin is dissolved in anhydrous methanol, Tween 80 and water.

7. The method for preparing a composite aerogel loaded with curcumin according to claim 1, characterized in that: The mass ratio of the pineapple leaf cellulose to chitosan is 1-4:6:

9.

8. The method for preparing a composite aerogel loaded with curcumin according to claim 1, characterized in that: The freeze drying process specifically includes pre-freezing at -20°C for 10-14 hours, freezing again at -80°C for 3-5 hours, and vacuum freeze drying for more than 36 hours.

9. A composite aerogel loaded with curcumin, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the composite aerogel loaded with curcumin as claimed in claim 9 in preparing a food preservative.